Paradoks Komitmen dalam TQM: Eksplorasi Hubungan antara Psychological Ownership dan Zero Defect - Kisma Dian; Putri Rizkiyah; Talita Adelia Zahira; Sasha Salsabilah; Mukhtaruddin, Mukhtaruddin (GLOBAL SCIENTS PUBLISHER, 2026)
In global business dynamics, the integration of quality management systems and organizational behavior plays a key role in sustaining quality standards. The relationship between Psychological Ownership and the zero-defect principle in Total Quality Management (TQM) highlights the importance of individual psychological factors beyond technical procedures. This phenomenon reflects a “commitment paradox,” where strict structural controls and standardized processes are required to minimize errors, yet success largely depends on employees’ intrinsic motivation and sense of ownership. Literature synthesis indicates that individuals with strong Psychological Ownership demonstrate greater responsibility and proactively prevent errors. Integrating organizational behavior with quality management perspectives suggests that aligning TQM structures with Psychological Ownership can strengthen sustainable quality performance and organizational competitiveness.